Missiological Dialogue in Strategic Decision-Making of the School Principal: A Qualitative Study at UPT SDN 076 Siponjot, Lintongnihuta District, Humbang Hasundutan Regency - Dapot Damanik; Dinar Sianturi; Yohana Nelly Panjaitan; Alex Bob Siringoringo; Kristina Saragih (Sean Institute, 2026)
This article explores the integration of